Association of the APOE ε4 allele with disease activity in multiple sclerosis. Issue 2 (1st August 1999) - Evangelou, Nikos; Jackson, Mandy; Beeson, David; Palace, Jackie
Abstract : OBJECTIVES: Allelic variants of the APOE gene are known to influence the course of many neurological diseases and there is increasing evidence that apolipoprotein E (APOE) is a pivotal component in reinnervation and dendritic remodelling after neuronal injury. Previous studies did not show significant differences in the APOE allele frequencies in multiple sclerosis compared with controls but did not examine for correlation with disease severity. This study explores the relation of APOE genotypes with the disease severity. METHODS: Ninety five patients with multiple sclerosis were studied. Age of onset, type, and activity of the disease were recorded prospectively and genotyping was performed according to standard protocols. RESULTS: APOE allele frequencies of the group as a whole, the relapsing group, or the primary progressive group were not significantly different from those reported from matched historical controls. The ε4 allele was found to be more common in patients with a more aggressive type of multiple sclerosis (odds ratio=2.95, p=0.03). CONCLUSIONS: Although APOE does not seem to be implicated in the early pathogenesis of the disease, patients possessing the ε4 allele might have a reduced capacity for neuronal remodelling after relapses.